2017
DOI: 10.1103/physrevb.96.024424
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic measurements of the spin Peltier effect in metal/yttrium-iron-garnet junction systems

Abstract: The spin Peltier effect (SPE), heat-current generation due to spin-current injection, in various metal (Pt, W, and Au single layers and Pt/Cu bilayer)/ferrimagnetic insulator (yttrium iron garnet: YIG) junction systems has been investigated by means of a lock-in thermography (LIT) method. The SPE is excited by a spin current across the metal/YIG interface, which is generated by applying a charge current to the metallic layer via the spin Hall effect. The LIT method enables the thermal imaging of the SPE free f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(104 citation statements)
references
References 85 publications
5
99
0
Order By: Relevance
“…This value is almost same as the value obtained in the thermographic experiments [17,19]; since in Ref. [19] the sine-wave amplitude A of ∆T SPE is divided by the rectangular-wave amplitude of ∆j c , a correction factor of π/4 is necessary, i.e. ∆T SPE /∆j c = πA/ (4∆j c ) = 3.7 × 10 −13 Km 2 /A in the previous study.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This value is almost same as the value obtained in the thermographic experiments [17,19]; since in Ref. [19] the sine-wave amplitude A of ∆T SPE is divided by the rectangular-wave amplitude of ∆j c , a correction factor of π/4 is necessary, i.e. ∆T SPE /∆j c = πA/ (4∆j c ) = 3.7 × 10 −13 Km 2 /A in the previous study.…”
Section: Resultssupporting
confidence: 80%
“…While (i) is not well experimentally investigated, the existence of the µm-range length scale in the SPE [19] and the similarity between δ SPE and δ SSE suggest the dominant contribution from (ii) as in the case of the SSE [25,30]. In fact, recently, it has been demonstrated that the high magnetic fields reduce the propagation length of magnons contributing to the SSE [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process accompanies a heat flow J q between the PM/FI and thereby modulates the system temperature. The SPE-induced temperature modulation ∆T SPE satisfies the following relation [36][37][38]…”
Section: Methodsmentioning
confidence: 99%
“…Although experimental evidence of both effects has been already obtained [16,17], the quantitative demonstration of their reciprocity, the relation between the two effects and the connection with intrinsic properties of the layers, has yet to be proven [13,18,19,20].…”
Section: Introductionmentioning
confidence: 99%